A Comparative Study of the Physical Creation of Soul in Islamic Theology and Transcendent Theosophy - Mostafa Azizi Alvijeh (آموزه‌‌های فلسفه اسلامي)
One of the common topics of Islamic theology and transcendent theosophy or al-ḥikmat al-muta’āliyah (Arabic: الحکمة المتعالیة) is the “physical creation of soul”. There are two incidental and original approaches in this regard In Islamic theology: the incidental approach considers the soul conditioned on moderate temperament in the body to be created (originated) and the original approach considers the soul like other bodies and considers it as an originated object in an absolute manner. The original view of the soul has also offered different interpretations about the mode of creation (origination): Being accident, sameness with perceptible (sensible) temple, being rarefied body (subtle body), the main part of the body and being indivisible part of soul. The main reason of theologians for creation based on the incompatibility of pre-eternity of the soul with attributes such as the Almighty and All-Powerful for God. In contrast, Mullā Ṣadrā believes in the incompatibility between the temporal contingency (temporal origin) of the soul and its innate immateriality and emphasizes the idea of “corporeality of creation and the spirituality of continuance” (Arabic: جسمانیة الحدوث و روحانیة البقاء). The research is a comparative study and analysis of Islamic theology and transcendent theosophy in the problem of createdness of the soul (temporality of the soul). The difference between theological and philosophical approaches goes back to the ontological and anthropological principles of them. The theory of the soul corporeality creation in theology and philosophy in addition to sharing in some essential concomitants has different consequences such as differences in the criterion of personal identity. The soul corporeality creation from the perspective of Islamic theology and transcendent theosophy by an analytical and comparative method has been analyzed in this article and the intersection points and their distinction are highlighted in the principles and essential concomitants.